Jurnalis Data : Satu Data Indonesia (SDI) Lemah Data - Maulana Arief; Amalia Nurul Muthmainnah (LPPM Stikosa - AWS, 2021)
ABSTRACT The government built Satu Data Indonesia (SDI) as part of implementing the principle of open government. Through SDI, all data from the government from in Indonesia including data from government agencies can be easily accessed by visiting the data.go.id website. This situation should be a good ecosystem to develop data journalism in Indonesia, because the government provides abundant data. This study aims to see the implementation of SDI from the perspective of data journalists. Data journalist is a profession that is directly related to SDI, they are tasked with managing data to be presented to the public in a simple and easy-to-understand manner for the general public. By interviewing data journalists from Katadata and Lokadata (two online media who declare themselves as data journalism), this qualitative research is expected to provide constructive input on the implementation of One Data Indonesia. In general, the existence of SDI is appreciated by data journalists. But data journalists from Katadata and Lokadata do not use SDI as part of their news-seeking activities. They see SDI has basic problems, the lack of data availability, data relevance problems, problems with easy data access, no data updates (updates) to data reliability. In addition, problems with data updating and data reliability, on the other hand, not all regions in Indonesia are connected to SDI. As a result, data journalists do not use Satu Data Indonesia as an instrument to make news. They prefer to dig up data through data mining on the internet and collect data gradually in their data bank for processing at a later date. Keywords: One Data Indonesia, Open Government, Online Media, Data Journalism